Building complex carbon skeletons with ethynyl[2.2]paracyclophanes - Dix, Ina; Bondarenko, Lidija; Jones, Peter G.; Oeser, Thomas; Hopf, Henning (Beilstein Journal of Organic Chemistry, 2014)
Ethynyl[2.2]paracyclophanes are shown to be useful substrates for the preparation of complex, highly unsaturated carbon frameworks. Thus both the pseudo-geminal- 2 and the pseudo-ortho-diethynylcyclophane 4 can be dimerized by Glaser coupling to the respective dimers 9/10 and 11/12. Whereas the former isomer pair could not be separated so far, the latter provided the pure diastereomers after extensive column chromatography/recrystallization. Isomer 11 is chiral and could be separated on a column impregnated with cellulose tris(3,5-dimethylphenyl)carbamate. The bridge-extended cyclophane precursor 18 furnished the ring-enlarged cyclophanes 19 and 20 on Glaser–Hay coupling. Cross-coupling of 4 and the planar building block 1,2-diethynylbenzene (1) yielded the chiral hetero dimer 22 as the main product. An attempt to prepare the biphenylenophane 27 from the triacetylene 24 by CpCo(CO)2-catalyzed cycloisomerization resulted in the formation of the cyclobutadiene Co-complex 26. Besides by their usual spectroscopic and analytical data, the new cyclophanes 11, 12, 19, 20, 22, and 26 were characterized by X-ray structural analysis.
Keywords: carbon-rich molecules; complex carbon scaffolds; cyclophanes; Glaser coupling; multibridged cyclophanes; X-ray analysis